KRITIK TERHADAP SISTEM EKONOMISOSIALIS DAN KAPITALIS - M. Sholahuddin (Muhammadiyah University Press, 2001)
The failure of economic capitalism system stated by Adam Smith (1723-1790) and David Ricardo (1772-1823) actually have been criticized by Karl Marx (1818-1883) in his book